Pengaruh Media Engcita (Engklek Cinta Tanah Air) Terhadap Pendidikan Karakter Di Kelas IV SD Negeri 101910 SidodadiDesa Pasar Miring - Cindy Awaliyah; Wahyu Hidayat; Syarifah Ainun Harahap (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2024)
The Influence of Engcita Media (Engklek Cinta Tanah Air) on Character Education of Class IV at SD Negeri 101910 Sidodadi, Pasar Miring Village, Academic Year 2024. Thesis: Medan, Elementary School Teacher Education Study Program, Faculty of Education, Nahdlatul Ulama University of North Sumatra (Supervisors: Wahyu Hidayat, S.Pd., M.Pd and Syarifah Ainun Harahap, S.Pd, M.Pd), This study aims to determine the effect of engcita media (engklek cinta tanah air) on character education of grade IV at SD Negeri 101910 Sidodadi. The number of students studied in the experimental class was 26 people and in the control class was 27 people. In this study, the method used was the experimental method. The population taken in this study were all grade IV students at SD Negeri 101910 Sidodadi. The variables of this study consisted of independent variables, namely the use of engcita media and dependent variables, namely character education of grade IV students at SD Negeri 101910 Sidodadi. Data collection techniques used test, observation, and documentation methods. In the experimental group, the average pre-test score was 63.27 and the post-test score was 74.81. In the control group, the average pre-test score was 62.22 and the post-test score was 70.93. The results of the hypothesis test showed that the significance value was 0.01 <0.05. From these results, it can be concluded that the use of Engcita media has a positive influence on the character education of fourth grade students of SD Negeri 101910 Sidodadi.